Moral Value and Image of Women in The Novel of The Single Parasite Ayu Utami's Work - Emalia Nova Sustyorini; Haris Supratno (Institute of Computer Science (IOCS), 2021)
The purpose of this research is to describe the moral values ??and images of women contained in the novel The single parasite by Ayu Utami. This research uses a descriptive qualitative approach. The object and subject of this research study is Ayu Utami's novel Si ParasitLajang, published in 2013. The data of this study are the moral values ??and images of women contained in the novel The single parasite by Ayu Utami. The data source of this research is Ayu Utami's novel Si ParasitLajang. The data collection technique is done by reading the object of study in depth accompanied by an understanding of the moral values ??and images of women in the novel. This qualitative research data analysis technique is inductive in nature, namely an analysis based on the data obtained first by classifying the data that has been recorded in the data recording list for existing categories or classifications, the second data that has been classified is further analyzed to be used as a basis for interpretation all data and the third then concludes the research results. The results of the research on the moral values ??and images of women in the novel The single parasite by Ayu Utami are (1) the moral values ??in the novel The single parasite by Ayu Utami, namely: being responsible for the family, loyal, and care. (2) the image of women in the novel The single parasite by Ayu Utami is an educated woman, a woman who isindependent, women who have a high social life, beautiful women, ugly women, married women, single women, metropolitan women, brave women, and critical thinking women.